(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
We report on an experimental campaign designed to shed light on critical nonlinear hydrodynamic effects of heaving wave energy converter (WEC) buoys undergoing large-amplitude motions in operational conditions. The experiments carried out with a spherical model comprised radiation, diffraction and combined tests, where the vertical motion was prescribed and delivered via an actuator. As such, we had independent control of incident waves and motions, enabling isolation of different nonlinear terms by combining recordings from multiple phase- and amplitude-manipulated runs. All tests utilised short-duration wave groups and/or corresponding transient motion signals. We focus on analysis of nonlinear changes in the hydrodynamic forces, and free surface, in the first-harmonic frequency range - this is of most importance to WECs. In a series of radiation experiments, with progressively increasing imposed motions, the radiated wave field and the force in phase with the body velocity are found to decrease nonlinearly, pointing to the WEC’s reduced ability to radiate waves under larger oscillations. In the combined tests, we are able to isolate various high-order cross-terms. We attempt to explain the observed trends through third-order potential flow interactions and consider a simple method to approximately describe these.